Annual Plan 2008-09 Volume - III (Statements) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2008)
Annual Plan 2008-09-Proposed Outlays (Sector-Wise), Annual Plan 2008-09-Proposed Outlays (Scheme-Wise), Annual Plan 2008-09 Statement Regarding Externally Aided Projects, Proposed Annual Plan -2008-09 Centrally Sponsored Schemes-Economic Services, Annual Plan -2008-09 Centrally Sponsored Schemes-Social Service, Annual Plan (2008-09)-Financial Outlays-Proposals For TSP Tribal Sub-Plan (TSP)-I, Annual Plan (2008-09) Scheduled Caste Sub-Plan (SCSP)-I Financial Outlays -Proposals For SCSP.
Planning Department, Government of Andhra Pradesh